Strengthening Visual Communication Skills for Deaf Friends at The As-Sami Tuli Foundation (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
The Student Internship Program (KKM) was held at the As-Sami Tutoring Foundation in Pontianak, West Kalimantan, in July 2025. The goal was to improve the visual communication skills of deaf learners as a means of empowerment and to support inclusive learning practices. Visual communication plays a central role for individuals with hearing impairments in understanding information and interacting socially. The program consisted of three main participatory activities: delivering instructions through sign language, a picture-guessing game, and a handicraft workshop. All activities emphasized hands-on practice tailored to the participants' visual learning characteristics. The results showed a high level of enthusiasm and engagement, with participants demonstrating improved understanding of visual symbols, shapes, and colors, as well as increased self-confidence and social interaction. The program made a positive contribution to strengthening visual communication skills and fostering an inclusive learning environment.